(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2025)
With the emergence and wide scale adaptation of social media as a means for mass communication, our world has transformed into a digital globe with almost no geographical or cultural barriers. This paper aims at evaluating the impact caused by social media in a democratic society, determining the extent of the impact and assessing its effectiveness over traditional methods of mass communication by analyzing and interpreting the pre existing records on this subject.